Early-onset dementia and extrapyramidal disease: clinicopathological variant of Gerstmann-Straussler-Scheinker or Alzheimer's disease?. Issue 11 (November 1990) - Hart, J; Gordon, B
Abstract : A case of progressive dementia and extrapyramidal signs beginning at age 29, with a ten year course until death, is presented. Necropsy examination showed an assortment of plaque types (including striatal plaques), neurofibrillary tangles, granulovacuolar degeneration, and depigmentation of the substantia nigra and locus ceruleus. This case had pathological features found in both Gerstmann-Straussler-Scheinker disease and in Alzheimer's disease. While somewhat similar to several other cases with features of both diseases, it differs in the presence of dystonia and striatal plaques. Although such cases may be difficult to categorize at present, they must be considered in the differential diagnosis of early onset dementia.